Highly diastereoselective and regioselective copper-catalyzed nitrosoformate dearomatization reaction under aerobic-oxidation conditions - Yang, Weibo; Huang, Long; Yu, Yang; Pflästerer, Daniel; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2014)
An unprecedented copper-catalyzed acylnitroso dearomatization reaction, which expands the traditional acylnitroso ene reaction and acylnitroso Diels-Alder reaction to a new type of transformation, has been developed under aerobic oxidation. Intermolecular and intra-/intermolecular reaction modes demonstrate an entirely different N- or O-acylnitroso selectivity. Hence, we can utilize this reaction as a highly diastereoselective access to a series of new pyrroloindoline derivatives, which are important structural motifs for natural-product synthesis.
Gesehen am 31.07.2020